Hydrophilic polymer‐coated PVC surface for reduced cell and bacterial adhesions. Issue 1 (6th February 2022) - Almousa, Rashed; Wen, Xin; Na, Sungsoo; Anderson, Gregory; Xie, Dong
Abstract: Hydrophilic polymers are very useful in biomedical applications. In this study, biocompatible polyethylene glycol (PEG) and polyvinylpyrrolidone (PVP) polymers end‐capped with succinimidyl groups were either modified or synthesised and attached to polyvinylchloride surfaces. The modified surfaces were evaluated with cell adhesion and bacterial adhesion. 3T3 mouse fibroblast cells and three bacteria species were used to evaluate surface adhesion activity. Results showed that the modified surface exhibited significantly reduced 3T3 cell adhesion with a 50%–69% decrease for PEG and a 64%–81% for PVP, as compared to unmodified polyvinylchloride. The modified surface also showed significantly reduced bacterial attachment with 22%–78%, 18%–76% and 20%–75% decrease for PEG and 22%–76%, 18%–76% and 20%–73% for PVP to Staphylococcus aureus, Escherichia coli and Pseudomonas aeruginosa, respectively, as compared to unmodified polyvinylchloride. It seems that an appropriate chain length or molecular weight (neither the longest nor the shortest chain length) determines the lowest cell and bacterial adhesion in terms of PEG. On the other hand, a mixture of polymers with different chain lengths exhibited the lowest cell and bacterial adhesion in terms of PVP.